Antibiotic resistome biomarkers and determinants in lettuce planting soil amended with β-lactam pharmaceutical fermentation residues - Ruiqi Wan; Kaixuan Zheng; Tianyu Chen; Yanping Xun; Jitao Lv; Lingyi Meng; Yufei Yang; Xuemei Zhu (Bioresource Technology, 2027)

Expansion of the rhizosphere soil and phyllosphere bacterial resistomes following repeated farmland application of high-temperature granulation-treated antibiotic fermentation residues - Ruiqi Wan; Tianyu Chen; Yanping Xun; Yazhuo Chen; Jitao Lv; Lingyi Meng; Kristian Koefoed Brandt; Yawei Wang (Journal of Environmental Sciences, 2026)

A Novel, Dual-Response Chemosensor Based on Ferrocene Derivative for the Selective Detection of Al3+ Ions : Fluorescence and Electrochemical Signaling - Wenqin Liu; Yanping Liu; Zenghui Li; Santai Zou; Pingnan Wan; Yan Lin (Journal of Fluorescence, 2025)

Dynamic response analysis of topside transportation using SPMT - Ming Qiu; Min Zeng; Mingzhi Li; Yibin Lv; Changwei wan; Zhengang Wang; Yanping He (Ocean Engineering, 2025)

Resveratrol inhibits autophagy in cardiomyocytes subjected anoxia/reoxygenation injury: involved in VDAC1/PINK1/Parkin pathway - Ying Zhou; Yongzhe Huang; Haiyan Liang; Xiaomei Yang; Shulin Zhang; Yinru Huang; Yanping Wan; Hangfei Zhou; An Huang; Yue Chen; Xiao Li; Yian Peng; et al. (Toxicology and Applied Pharmacology, 2025)

Trait segregation and growth characteristics of the F2 generation hybrids between Crassostrea dianbaiensis and C. iredalei - Jiangwei Li; Ying Pan; Qinggan Xing; Jinhui Wu; Haitao Ma; Weitao Wan; Chao Yue; Zhongyu Wang; Jun Li; Ziniu Yu; Yanping Qin; Yuehuan Zhang (Aquaculture International, 2025)

Hybrid Path Planning Method for USV Based on Improved A-Star and DWA - Yan Liu; Zeqiang Sun; Junhe Wan; Hui Li; Delong Yang; Yanping Li; Wei Fu; Zhen Yu; Jichang Sun (Journal of Marine Science and Engineering, 2025)
This paper presents a hybrid path planning method that integrates an enhanced A-Star algorithm with the Dynamic Window Approach (DWA). The proposed approach addresses the limitations of conventional A-Star algorithms in global path planning, particularly their inability to adaptively avoid obstacles in real-time. To improve navigation safety, the A-Star search strategy is enhanced by avoiding paths that intersect with obstacle vertices or pass through narrow channels. Additionally, a node optimization technique is introduced to remove redundant nodes by checking for collinearity in consecutive nodes. This optimization reduces the path length and ensures that the path maintains a safe distance from obstacles using parallel lines. An advanced Bézier curve smoothing method is also proposed, which adaptively selects control points to improve path smoothness and driving stability. By incorporating these improvements, the enhanced A-Star algorithm is combined with DWA to facilitate dynamic obstacle avoidance while generating global paths. The method accounts for the kinematic characteristics of the USV, as well as physical constraints such as linear and angular velocities, enabling effective handling of obstacles in dynamic environments and ensuring safe navigation. Simulation results demonstrate that the proposed algorithm generates secure global paths, significantly optimizing node count, path length, and smoothness, while effectively avoiding dynamic obstacles, thus ensuring safe navigation of the USV.

Critical review on food packaging strategy against spoilage - Lei Liu; Youwei Jiang; Kun Wan; Yanping Wei; Du Tuo; Chuanqin Zhou; Quanguo He; Yimin Tan (Food and Humanity, 2025)

Offspring performance of backcrossing between hybrid line of Crassostrea dianbaiensis ♀ × Crassostrea iredalei ♂ and their parental species - Jiangwei Li; Yanping Qin; Qinggan Xing; Jinhui Wu; Haitao Ma; Weitao Wan; Chao Yue; Zhongyu Wang; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Aquaculture, 2025)

Growth performance of two brackish oysters (Crassostrea iredalei and Crassostrea dianbaiensis) and their hybrids in subtropical sea area - Jiangwei Li; Ying Pan; Jinhui Wu; Haitao Ma; Weitao Wan; Chao Yue; Shengyong Li; Zhongyu Wang; Jun Li; Ziniu Yu; Yanping Qin; Yuehuan Zhang (Aquaculture, 2025)

Genetic diversity and genetic structure in successive mass selected generations of tetraploid Pacific oysters (Crassostrea gigas), diploid Portuguese oysters (C. angulata) and their allotriploid oysters - Haitao Ma; Yanping Qin; Yinjie Zhang; Weitao Wan; Jingyue Huang; Na Mi; Zhen Zhao; Zhongyu Wang; Jiangwei Li; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2025)

Corrigendum to “Hybridization and growth characteristics of interspecific crosses between Crassostrea hongkongensis and Crassostrea iredalei” [Aquaculture, Volume 595, Part 2, 30 January 2025, 741656] - Jiangwei Li; Ying Pan; Qinggan Xing; Haitao Ma; Chao Yue; Weitao Wan; Jinhui Wu; Zhongyu Wang; Shengyong Li; Jun Li; Ziniu Yu; Yanping Qin; et al. (Aquaculture, 2025)

First successful inducing gynogenesis in Crassostrea angulata by inactivated tetraploid Crassostrea gigas sperm - Weitao Wan; Yanping Qin; Jinhui Wu; Haitao Ma; Chao Yue; Shengyong Li; Jiangwei Li; Zhongyu Wang; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; et al. (Aquaculture, 2025)

Hybridization and growth characteristics of interspecific crosses between Crassostrea hongkongensis and Crassostrea iredalei - Jiangwei Li; Ying Pan; Qinggan Xing; Haitao Ma; Chao Yue; Weitao Wan; Jinhui Wu; Zhongyu Wang; Shengyong Li; Jun Li; Ziniu Yu; Yanping Qin; et al. (Aquaculture, 2025)

Highly degradable bio-based plastic with water-assisted shaping process and exceptional mechanical properties - Jingjing Wang; Yuan Liang; Yuhan Chen; Hai Wan; Wenbin Jin; Ting Luo; Yuwei Chen; Peng Wei; Shuohan Huang; Yong He; Yanping Wang; Yumin Xia (Carbohydrate Polymers, 2025)

Ecologically friendly remediation of groundwater sulfamethoxazole contamination: Biologically synergistic degradation by thermally modified activated carbon-activated peracetic acid in porous media - Si Li; Ruizhe Xu; Luochao Wan; Chaomeng Dai; Jixiang Li; Xueji You; Yanping Duan; Xiaoying Lai; Zhi Li; Jifeng Guo; Yalei Zhang; Jiajun Hu; et al. (Journal of Hazardous Materials, 2024)

Corrigendum to “Genetic improvement of aquaculture performance for tetraploid Pacific oysters, Crassostrea gigas: A case study of four consecutive generations of selective breeding” [Aquaculture 563 (2023) 738910] - Weitao Wan; Yanping Qin; Gongpengyang Shi; Shengyong Li; Qingliang Liao; Haitao Ma; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Successive selection responses of tetraploid Crassostrea angulata: Comparison of growth, survival, sex ratio and ploidy composition between selected and unselected groups - Yanping Qin; Weitao Wan; Jiangwei Li; Chao Yue; Zhongyu Wang; Qinggan Xing; Haitao Ma; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Feasibility exploration and comparative analysis of interspecific hybridization between Crassostrea hongkongensis and Crassostrea dianbaiensis - Jiangwei Li; Yanping Qin; Zhongli Peng; Weitao Wan; Chao Yue; Zhongyu Wang; Haitao Ma; Qinggan Xing; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Aquaculture, 2024)

Growth, survival and reproductive traits of chemical induced and tetraploid-derived triploid Hong Kong oysters (Crassostrea hongkongensis) - Yanping Qin; Weitao Wan; Jiangwei Li; Zhongyu Wang; Haitao Ma; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Unlocking the power of activated carbon-mediated peracetic acid activation for efficient antibiotics abatement in groundwater: Coupling the processes of electron transfer, radical production, and adsorption - Si Li; Chaomeng Dai; Jixiang Li; Yanping Duan; Rongbing Fu; Yalei Zhang; Jiajun Hu; Lang Zhou; Luochao Wan; Qiming Zhang; Zhibo Zhang (Journal of Hazardous Materials, 2024)

Phenotypic traits of reciprocal tetraploid hybrids derived from tetraploid Crassostrea gigas and tetraploid Crassostrea angulata - Chao Yue; Yanping Qin; Weitao Wan; Gongpengyang Shi; Shengyong Li; Jiangwei Li; Zhongyu Wang; Haitao Ma; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Vascular plant communities and biocrusts act as controlling factors in mitigating soil erosion on the Great Wall in a semi-humid area of Northwestern China - Yanping Liu; Rongliang Jia; Wanfu Wang; Yuchen Wan; Yanhong Gao; Hongtao Zhan; Jing Ren; Zhang Chen; Fei Qiu; Jing Zhu (Science of The Total Environment, 2024)

Seismic response of a mid-story isolated structure considering SSI in mountainous areas under long-period earthquakes - Feng Wan; Shengwu Qin; Dewen Liu; Tiange Zhao; Yanping Zheng; Hang Shan; Zhiang Li; Fusong Peng; Jingran Xu; Min Lei (Earthquake Engineering and Engineering Vibration, 2024)

A facile two-step method to construct environmental-friendly Janus coconut wood membrane for oil/water separation - Wanfei Yu; Xue Hou; Yanping Zhang; Weimin Wan; Peng Gao; Zihao Yan; Jianbao Li; Xue Hou (Journal of Water Process Engineering, 2023)

Metabolomics and metatranscriptomics reveal the influence mechanism of endogenous microbe (Staphylococcus succinus) inoculation on the flavor of fermented chili pepper - Yumeng Li; Xiaoqin Luo; Huan Guo; Jinrong Bai; Yue Xiao; Yuan Fu; Yanping Wu; Hongyu Wan; Yina Huang; Hong Gao (International Journal of Food Microbiology, 2023)

Drought characteristics and dominant factors across China: Insights from high-resolution daily SPEI dataset between 1979 and 2018 - Lingling Wan; Virgílio A. Bento; Yanping Qu; Jianxiu Qiu; Hongquan Song; RongRong Zhang; Xiaoping Wu; Feng Xu; Jinkuo Lu; Qianfeng Wang (Science of The Total Environment, 2023)

Studies of interspecific backcross between hybrids of (Crassostrea angulata ♀ × C. gigas ♂) and their two parental species - Gongpengyang Shi; Yanping Qin; Weitao Wan; Shengyong Li; Qingliang Liao; Haitao Ma; Jun Li; Yunqing Li; Yinyin Zhou; Yuehuan Zhang; Ziniu Yu (Aquaculture, 2023)

Preparation of recyclable and deformable POM microfiber for oil–water separation with nature-inspired top–bottom strategy - Wenbin Jin; Jingjing Wang; Hai Wan; Yuan Liang; Shuohan Huang; Yuwei Chen; Peng Wei; Qun Shao; Yanping Wang; Yong He; Yumin Xia (Chemical Engineering Journal, 2023)

Hormonal Profiling of Encapsulated and Nonencapsulated Rhizomes of Chinese Cymbidium in Different Storage Environments - Shuangbin Fu; Zhuang Zhou; Yanping Yang; Zhen Ying; Wan Xu (Journal of Plant Growth Regulation, 2023)

Comparative analysis of growth, survival and sex proportion among tetraploid-based autotriploid (Crassostrea gigas and C. angulata) and their allotriploid oysters - Yanping Qin; Gongpengyang Shi; Weitao Wan; Shengyong Li; Yunqing Li; Jun Li; Haitao Ma; Yuehuan Zhang; Ziniu Yu (Aquaculture, 2023)

Feasibility of interspecific hybridization between Iwagaki oyster, Crassostrea nippona and Portuguese oyster, Crassostrea angulata - Shengyong Li; Yanping Qin; Gongpengyang Shi; Weitao Wan; Qingliang Liao; Haitao Ma; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Aquaculture, 2023)

Genetic improvement of aquaculture performance for tetraploid Pacific oysters, Crassostrea gigas: A case study of four consecutive generations of selective breeding - Weitao Wan; Yanping Qin; Gongpengyang Shi; Shengyong Li; Qingliang Liao; Haitao Ma; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2023)

Comparison of biochemical composition, nutritional quality, and metals concentrations between males and females of three different Crassostrea sp. - Yanping Qin; Ru Li; Qingliang Liao; Gongpengyang Shi; Yinyin Zhou; Weitao Wan; Jun Li; Haitao Ma; Yuehuan Zhang; Ziniu Yu (Food Chemistry, 2023)

Microplastic Contamination on the Beaches of South China - Bingwen Chai; Yanping Li; Li Wang; Xiao-Tan Zhang; Yi-Ping Wan; Fengyuan Chen; Jie Ma; Wenlu Lan; Ke Pan (Frontiers in Marine Science, 2022)
Microplastics (MPs) have emerged as a pollutant of significant global concern. The sandy beach is a fragile environment that deserves our special attention with regard to MP contamination, as this area is a hotspot that accumulates large quantities of plastic waste. Notably, our current understanding of the MP distribution on beaches and the scale of contamination is far from sufficient. Hence, this study investigated the occurrence and characteristics of MPs on 14 beaches along the coast of South China. The MPs were ubiquitously distributed in the sand, most were small, less than 1 mm. A total of 18 types of polymers were identified in the sand, suggesting that diverse types of MPs are present on the beaches. Polyethylene, polypropylene, and polystyrene were the dominant types of MPs in most of our sampling sites. The MP abundance was higher in the upper layers (0–20 cm) of the beach than in the deeper layers (20–40 cm) of the sampling site when characterized by depth (Yangjiang beach). Our study demonstrates the extent and severity of MP pollution on the beaches of South China and provides implications for future remediation measures. More effort is needed to clarify the vertical distribution of MPs on beaches, especially for those MPs less than 1 μm.

Simvastatin Blocks Reinstatement of Cocaine-induced Conditioned Place Preference in Male Mice with Brain Lipidome Remodeling - Wei Xu; Yuman He; Jiamei Zhang; Hongchun Li; Xuemei Wan; Menglu Li; Yonghai Wang; Rui Xu; Haoluo Zhang; Yanping Dai; Haxiaoyu Liu; Linhong Jiang; et al. (Neuroscience Bulletin, 2021)

The Sesuvium portulacastrum Plasma Membrane Na+/H+ Antiporter SpSOS1 Complemented the Salt Sensitivity of Transgenic Arabidopsis sos1 Mutant Plants - Yang Zhou; Xiaochang Yin; Shumin Wan; Yanping Hu; Qing Xie; Ruimei Li; Baibi Zhu; Shaoping Fu; Jianchun Guo; Xingyu Jiang (Plant Molecular Biology Reporter, 2018)

A Comprehensive Analysis of Carotenoid Cleavage Dioxygenases Genes in Solanum Lycopersicum - Yanping Wei; Hongjian Wan; Zhiming Wu; Rongqing Wang; Meiying Ruan; Qingjing Ye; Zhimiao Li; Guozhi Zhou; Zhuping Yao; Yuejian Yang (Plant Molecular Biology Reporter, 2016)

γ-Aminobutyric acid (GABA) homeostasis regulates pollen germination and polarized growth in Picea wilsonii - Yu Ling; Tong Chen; Yanping Jing; Lusheng Fan; Yinglang Wan; Jinxing Lin (Planta, 2013)

Growth and yield of oleic sunflower (Helianthus annuus L.) under drip irrigation in very strongly saline soils - Shuqin Wan; Yanping Jiao; Yaohu Kang; Shufang Jiang; Junli Tan; Wei Liu; Jing Meng (Irrigation Science, 2013)

Gametophytically alloplasmic CMS line of rice (Oryza sativa L.) with variant orfH79 haplotype corresponds to specific fertility restorer - Shaoqing Li; Yanping Tan; Kun Wang; Cuixiang Wan; Yingguo Zhu (Theoretical and Applied Genetics, 2008)